Honor lost - Caine, Rachel (Caine, Rachel. Honors., 2020)
Zara Cole may have finally met her match. Lifekiller--a creature that can devour entire planets--is spreading terror throughout the universe, and it seems nothing can stand in the monstrous god-king's way. Reeling from a series of battles, Zara and her wounded band of allies are going to need a strategy before they face Lifekiller again. Zara's street smarts may not be enough when their enemy could be anywhere, destroying civilizations and picking his teeth with the bones. And just when it feels like she's reached a special place in her bond with Beatriz and Nadim, an ex from Earth with an ax to grind comes after her with nefarious intentions. With human enemies, alien creatures and mechanical stalkers on her tail, it comes down to the wire for Zara to save the galaxy--and the people she calls home--before the god-king consumes them all.